Non-pharmacological public health measures: Assessment of the PAHO Guide on outbreak and epidemics risk communication (Revista Contexto & Saúde, 2026)
The purpose of this article is to present an evaluability study of the Guide to Non-Pharmacological Public Health Measures prepared in 2020 by PAHO in order to maximize its usefulness in risk communication in outbreak and epidemic situations. A descriptive-qualitative approach was adopted, guided by the steps: (a) Documentary research; (b) Intervention modeling; (c) Extraction of evidence on the actions proposed in the document; (d) Validation of the logical theoretical model; (e) Elaboration of evaluative questions. Documentary analysis pointed to a multiplicity of actions to reduce community transmission, prioritizing the involvement of society, in addition to governmental and non-governmental institutions. The validated logical theoretical model made it possible to identify elements that could be useful as lessons to strengthen preparedness, preparedness and response capacities within the Health System in relation to disasters and other public health emergencies.
Keywords: Risk communication; Outbreaks and pandemics; Evaluability